Bundling crop diversification, nutrition and market interventions in farmer-led participatory experiments in Bangladesh: Pre- and post-season survey protocol - Cheesman, Stephanie; Nandi, Ravi; Hossain, Md. Khaled; Shahrin, Sumona; Krupnik, Timothy J. (TAFSSA, 2023)
Interdisciplinary research aimed at identifying effective strategies to enhance farmers' profits, improve the yield of nutritious crops, conserve natural resources, and sustain or enhance ecological services, all while mitigating greenhouse gas emissions from agricultural landscapes, is currently underway in Northern Bangladesh. To achieve real-world impact, research aims at generating evidence-based and actionable recommendations that can be being put into practice through both public and private auriculate extension networks, along with support for policy design and reform. Of particular interest is the ways in which farmer participatory research conducted by Transforming Agrifood Systems in South Asia (TAFSSA) can address methods and systems to improve the effectiveness of nutrition awareness and the marketing of diversified and nutritious crop products by farmers. This document provides brief updates on ongoing research while describing and providing the survey instruments and approaches being used.